The value of humanity in Kant's moral theory - Dean, Richard (Clarendon Press ; Oxford University Press, 2006)
The humanity formulation of Kant's Categorical Imperative demands that we treat humanity as an end in itself. Because this principle resonates with currently influential ideals of human rights and dignity, contemporary readers often find it compelling, even if the rest of Kant's moral philosophy leaves them cold. Moreover, some prominent specialists in Kant's ethics recently have turned to the humanity formulation as the most theoretically central and promising principle of Kant's ethics. Nevertheless, despite the intuitive appeal and the increasingly recognized philosophical importance of the humanity formulation, it has received less attention than many other, less central, aspects of Kant's ethics. Richard Dean offers the most sustained and systematic examination of the humanity formulation to dat